(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
General Background: YouTube has become a prominent media platform, serving various user needs, including entertainment, information, and profit generation for content creators, commonly known as YouTubers. Specific Background: Among the diverse range of YouTubers, some, like Windah Basudara, have generated controversial content characterized by toxic language and trash talking. Knowledge Gap: Despite the prevalence of toxic messages in online content, there is limited scholarly analysis focusing on how such language is represented and its implications in the context of YouTube. Aims: This study aims to analyze the representation of toxic messages in Windah Basudara’s content using Roland Barthes’ semiotic analysis framework. Results: Employing a descriptive qualitative approach, data were extracted from video clips featuring Windah Basudara. The analysis revealed that his use of toxic language serves as an emotional outburst, yet the vocabulary often conflicts with societal language ethics. Novelty: This research contributes to the understanding of the semiotic representation of toxicity in digital content, offering insights into the intersection of emotional expression and ethical communication. Implications: The findings underscore the need for critical engagement with language use in online platforms, which may inform future discussions on content moderation and the impact of YouTube creators on audience perceptions. Highlights: • Diverse User Engagement: YouTube serves various audiences, including those seeking entertainment and profit-driven content creators. • Controversial Content: Windah Basudara’s use of toxic language exemplifies emotional expression but often violates societal language ethics. • Critical Analysis Importance: The study emphasizes the necessity of understanding toxic language representation to guide discussions on content moderation and creator responsibility. Keywords: YouTube, Toxic Language, Semiotics, Content Analysis, Digital Communication